2022
DOI: 10.1111/1759-7714.14788
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size, but not consolidation‐to‐tumor ratio, is an independent prognostic factor for part‐solid clinical T1 non‐small cell lung cancer

Abstract: Background Tumor size and consolidation‐to‐tumor ratio (CTR) are crucial for non–small cell lung cancer (NSCLC) prognosis. However, the optimal CTR cutoff remains unclear. Whether tumor size and CTR are independent prognostic factors for part‐solid NSCLC is under debate. Here, we aimed to evaluate the prognostic impacts of CTR and tumor size on NSCLC, especially on part‐solid NSCLC. Methods We reviewed 1366 clinical T1 NSCLC patients who underwent surgical treatment. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…3 Similarly, Isaka et al 22 reported that segmentectomy reached a higher 5-year OS than lobectomy for stage 0-I lung cancer with high comorbidities, but not for those with low comorbidities. NSCLC with pure solid nodules usually had older age, a higher smoking rate, and a higher proportion of SCC and other histologic subtypes than those with GGO component 6,23,24 Whether segmentectomy could achieve a better OS than lobectomy for pure solid NSCLC with poor conditions needed more studies.…”
Section: Discussionmentioning
confidence: 99%
“…3 Similarly, Isaka et al 22 reported that segmentectomy reached a higher 5-year OS than lobectomy for stage 0-I lung cancer with high comorbidities, but not for those with low comorbidities. NSCLC with pure solid nodules usually had older age, a higher smoking rate, and a higher proportion of SCC and other histologic subtypes than those with GGO component 6,23,24 Whether segmentectomy could achieve a better OS than lobectomy for pure solid NSCLC with poor conditions needed more studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our research revealed another significant factor affecting the prognosis of MWA patients is the size of the tumor. Clinically, the maximum diameter of the primary tumor plays a pivotal role in tumor TNM staging and has been affirmed as an independent prognostic factor in several studies concerning lung carcinoma ( 38 , 39 ). Simultaneously, larger-diameter tumors exhibit a significantly higher rate of recurrence after thermal ablation.…”
Section: Discussionmentioning
confidence: 99%
“…acknowledged that the CTR was an independent prognostic factor for the entire non-small cell lung cancer (NSCLC) population, but not for certain subtypes of NSCLC. Tumor size still holds significance for certain solid NSCLC cases ( 11 ). Hence, in clinical practice, even for pure ground-glass nodules (GGNs) detected on CT, it is important to consider multiple factors such as tumor diameter, serum tumor markers, maximum standardized uptake value on PET-CT, age, gender, smoking status, current extra-pulmonary cancer, air bronchogram and nodule size (p<0.05),circulating tumor cell,and others ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%